Aerobic Bacteria Associated with Symptomatic Gallstone Disease and their Antimicrobial Susceptibility in Western Nepal - Thapa, Sagun Bahadur; Bajracharya, Kishor; Kher, Yashwant Ramakrishan; Pant, Sushama Suresh; Gurung, Sanjay; Pudasaini, Rashmi (Journal of Lumbini Medical College, 2017)
Introduction: Gallstone disease is one of the most common diseases affecting the gastrointestinal tract. Biliary tract infection results from bile stasis due to chronic obstruction, mainly (80%) gallstones. Biliary obstruction increases ducal pressure, resulting in bacterial proliferation and dissemination. Proper guidelines for appropriate use of antibiotics in managing uncomplicated and complicated gallstone disease are lacking; on the other hand, the antibiotic usage for its management cover a broad spectrum of organism which may not be required most of the times. This study aims to determine the icrobiology of the bile culture and antimicrobial susceptibility in patients with symptomatic gallstone disease in our setup. Methods: This prospective study included patients admitted in surgery department with a diagnosis of symptomatic gallstone disease and subjected for laparoscopic or open cholecystectomy from 1st of October 2015 to 30thSeptember 2016. The intraoperative bile of patients subjected for cholecystectomy were cultured aerobically in Blood agar and MacConkey agar. The isolates were identified and tested for their sensitivity pattern. The data were collected, entered and then analyzed using SPSS version 23. The descriptive statistics were calculated. Results: Of the total 259 patients, bile culture was negative in 183 patients (70.7%) and was positive in only 76 patients (29.3%). pseudomonas was the most common cultured organism in 52(68.4%) patients. Other isolated organisms included E. Coli, Staphylococcus, Klebsiella, Enterococci, and Acinetobacter. Imipenem and amikacin were the most effective prophylactic antibiotics. Conclusion: Bile culture was negative in majority of patients with symptomatic gallstone disease. Few patients are positive in culture with predominantly Pseudomonal growth, mostly sensitive to amikacin or imipenem. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 50-54 DOI: https://doi.org/10.22502/jlmc.v4i2.89